Designing Android Based Augmented Reality Location-Based Service Application - Alim Hardiansyah (JOIN (Jurnal Online Informatika), 2017)
Android is an operating system for Linux based smartphone. Android provides an open platform for the developers to create their own application. The most developed and used application now is location based application. This application gives personalization service for mobile device user and is customized to their location. Location based service also gives an opportunity for the developers to develop and increase the value of service. One of the technologies that could be combined with location based application is augmented reality. Augmented reality combines the virtual world with the real one. By the assistance of augmented reality, our surrounding environment could interact in digital form. Information of objects and environment surround us could be added to the augmented reality system and presented.Â Based on the background, the writers tried to implement those technologies on now rapidly developing android application as a final project to achieve bachelor degree in Department of Informatics Engineering, Faculty of Information Technology and Visual Communication, Al Kamal Science and Technology Institute. This application could be functioned to locate school by using location based service technology with the assistance of navigational applications such as waze and google maps, in form of live direction process through the smartphone